1987
DOI: 10.1111/j.1365-2559.1987.tb02609.x
|View full text |Cite
|
Sign up to set email alerts
|

Vimentin: an evaluation of its role as a tumour marker

Abstract: Vimentin: an evaluation of its role as a tumour marker In this study we examined 198 sarcomas, 38 carcinomas, 13 'tumours with a spindle cell component' and 22 malignant melanomas with a commercial monoclonal virnentin antibody. All histopathological material was formalin fixed and paraffin embedded. The results show this antibody to be a sensitive and specific marker of mesenchymal derivation or differentiation. It is a useful tool in separating sarcomas from most carcinomas, and in separating malignant melan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
2

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(51 citation statements)
references
References 36 publications
0
49
0
2
Order By: Relevance
“…Vimentin is a structural protein from cells of mesenchymal origin (Leader et al, 1987). Its expression is higher in migratory epithelial cells and may contribute to the migratory and invasive phenotype of metastatic cells (Bindels et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Vimentin is a structural protein from cells of mesenchymal origin (Leader et al, 1987). Its expression is higher in migratory epithelial cells and may contribute to the migratory and invasive phenotype of metastatic cells (Bindels et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Intense immune-reaction of tumor cells to markers (vimentin, CD34, CD99, actin) that stain normal tissues and neoplasms of mesenchymal origin (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28); in contrast, they do not stain with cytokeratins, which represent a marker for epithelial differentiation. 2.…”
Section: Etio-pathogenetic Hypothesesmentioning
confidence: 99%
“…It provides flexibility to the cell, and integrity (Goldman et al 1996). Through the various experimental setups it has been found that it is used as a marker for sarcoma tumour to identify the mesenchyme (Leader et al 1987). Further investigation reveals that it regulates the interaction of various cytoskeletal proteins with that of cell adhesion molecules and thereby plays a pivotal role in migration, invasion, signalling and adhesion.…”
Section: Vimentinmentioning
confidence: 99%